Mechanical and Optical Properties of Thin Film Titanium Nitride (TiN) Resulting from Deposition DC Sputtering - Setyanjana, Andre Yoan; Melati, Asih; Aziz, Ihwanul (Proceeding International Conference on Science and Engineering, 2019)
Titanium nitride (TiN) thin film was successfully grown on the surface of stainless steel 304 (SS 304) and preparate glass using the direct current sputtering method. The fabrication was done at high voltage 2.5 kV, sputtering current 40 mA, and deposition time 1 hour. The characterization was carried out using a Micro Hardness Tester and UV-Vis Spectrophotometer. Based on mechanical properties, the hardness results of deposition on SS 304 obtained vickers hardness value of 153.59 HVN and thin film thickness was preparate glass 172.61 nm. Whereas optical properties, from testing the transmittance of thin films TiN measured at a wavelength range of 300 nm - 800 nm, the thin film TiN optical gap energy is 3.51 eV.